2018
DOI: 10.21315/mjms2018.25.6.5
|View full text |Cite
|
Sign up to set email alerts
|

Strobilanthes crispus Extract Reduces RespiStrobilanthes crispus Extract Reduces Respiratory Exchange Ratio in Obese Mice Fed High Fat and Low Fat Diets

Abstract: BackgroundStrobilanthes crispus (S. crispus) leaves were traditionally consumed for its body weight lowering effect. In this study, we investigated the anti-obesity effect of S. crispus leaves extract (SCE).MethodsMice (n = 48) were fed high-fat diet (HFD) for 25 weeks to induce obesity, after which half were maintained on HFD and half switched to low-fat diet (LFD)while they were given normal water (H2O) or 0.1% (w/v) SCE in water at week 0–4 which was increased to 1% (w/v) at week 5–9. Effects of treatment w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Consumption of a high-fat diet (HFD) causes increased lipid accumulation and contributes to various metabolic diseases such as obesity, hyperlipidemia, atherosclerosis, cardiovascular disease, type 2 diabetes mellitus and nonalcoholic fatty liver disease (NAFLD) (1)(2)(3)(4). HFD contains lipids that are metabolised into triglycerides and cholesterol through exogenous and endogenous pathways in the intestine and liver, respectively (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Consumption of a high-fat diet (HFD) causes increased lipid accumulation and contributes to various metabolic diseases such as obesity, hyperlipidemia, atherosclerosis, cardiovascular disease, type 2 diabetes mellitus and nonalcoholic fatty liver disease (NAFLD) (1)(2)(3)(4). HFD contains lipids that are metabolised into triglycerides and cholesterol through exogenous and endogenous pathways in the intestine and liver, respectively (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…These results suggested that Dyglomera ® can be used as an effective functional food for treating obesity. In addition, further studies such as a comprehensive laboratory animal monitoring system (CLAMS) [ 36 ] are needed to evaluate the effects of Dyglomera ® in activities, even circadian rhythms. Also, it is suggested that further mechanism studies through treatment with AMPK inhibitors such as compound C are needed to elucidate the AMPK-related anti-obesity biochemical mechanism of Dyglomera ® .…”
Section: Discussionmentioning
confidence: 99%